Answer:
Part 1) y=6
Part 2) y=-20
Step-by-step explanation:
Part 1) If y varies inversely as x, and y=3 as x = -2, find y for the x value of -1.
we know that
A relationship between two variables, x, and y, represent an inverse variation if it can be expressed in the form [tex]y*x=k[/tex] or [tex]y=k/x[/tex]
we have
For x=-2, y=3
Find the value of the constant k
[tex]k=y*x[/tex]
substitute the values of x and y
[tex]k=(3)(-2)=-6[/tex]
The equation is equal to
[tex]y=-6/x[/tex]
so
For x=-1
substitute in the equation and solve for y
[tex]y=-6/(-1)=6[/tex]
Part 2) If y varies directly as x, and y=15 as x=-3, find y for the x value of 4
we know that
A relationship between two variables, x, and y, represent a proportional variation if it can be expressed in the form [tex]y/x=k[/tex] or [tex]y=kx[/tex]
we have
For x=-3, y=15
Find the value of the constant k
[tex]k=y/x[/tex]
substitute the values of x and y
[tex]k=15/-3=-5[/tex]
The equation is equal to
[tex]y=-5x[/tex]
so
For x=4
substitute in the equation and solve for y
[tex]y=-5(4)=-20[/tex]